India in the Indian Ocean World - Mukherjee, Rila. author. aut Link
XXVI, 410 p. 55 illus., 23 illus. in color.
Keywords: The book integrates the latest scholarly literature on the entire Indian Ocean region, from East Africa to China. Issues such as India's history, India’s changing status in the region, and India's cross-cultural networking over a long period are explored in this book. It is organized in specific themes in thirteen chapters. It incorporates a wealth of research on India’s strategic significance in the Indian Ocean arena throughout history. It enriches the reader's understanding of the emergence of the Indian Ocean basin as a global arena for cross-cultural networking and nation-building. It discusses issues of trade and commerce, the circulation of ideas, peoples and objects, and social and religious themes, focusing on Hinduism, Buddhism, and Islam. The book provides a refreshingly different survey of India’s connected history in the Indian Ocean region starting from the archaeological record and ending with the coming of empire. The author’s unique experience, combined with an engaging writing style, makes the book highly readable. The book contributes to the field of global history and is of great interest to researchers, policymakers, teachers, and students across the fields of political, cultural, and economic history and strategic studies.